The financial feasibility analysis of seaweed product at ora food MSMEs in Yogyakarta - Intyas, Candra; Purwanti, Pudji; Tjahjono, Agus; Fadillah, Faizah Ajeng; Rifaldo, Ismail Sebastian (AGROMIX, 2025)
Introduction: Diversification of processed seaweed products aims to respond to changes in consumer preferences, reach a broader market, and reduce the risk of dependence on one particular product type. In addition, product diversification can also be a practical innovation in increasing public interest in fishery products. One is the Ora Food MSMEs Yogyakarta, which is in the form of seaweed chips. Business feasibility is needed in a company's progress, and it is an analysis carried out on agencies on a particular project to provide direction as to whether investment in the project is feasible or not. Therefore, this study aims to analyze financial feasibility and business sensitivity in Ora Food MSMEs. Methods: Profitability analysis (BEP, profit, R/C and RTC), financial feasibility (NPV, B/C, IRR and PP) and business sensitivity analysis. Results: Profitability analysis, namely BEP sales of Rp. 119,324,566 or selling as many as 6,609 pcs with the product that must be sold the most on the regular spicy seaweed chips product (BEPq KRLBP )  a total of 3,182 pcs R/C = 2.18 (>1), RTC = 95.42% (>6%) then financial feasibility is NPV = Rp. 747,908,878,- (NPV positive) Net B/C = 3.62 (>1) and IRR = 65% (>6%) and payback period = 1.65 years. Furthermore, the business sensitivity analysis uses three scenarios, namely (1) Costs increase (138%), benefits remain the same, (2) Costs remain the same, benefits decrease (41%), and (3) Costs increase (56%), Benefits decrease (31%). Conclusion: The results of the financial feasibility analysis show that the business is profitable in the short term and financially feasible. In the sensitivity analysis, it can be concluded that the company is quite sensitive if there is a decrease in benefits but is not sensitive to increasing costs. Therefore, sales are expected to be constant at current production or improved by using optimised social media online marketing to reach a larger market.